Learning from Malaysia's Progressive Islamic Law Framework on Online Gambling: Insights for Indonesia - Solehudin, Ending; Mustopa; Mudzakkir, Muhammad; Saepudin; Ahyani, Hisam (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Online gambling has become a rapidly growing issue, leading to financial losses and mental health challenges. In Malaysia, online gambling is regulated under progressive Islamic law which focuses on social justice, while Indonesia struggles with weak enforcement despite existing regulations. This study discusses three main parts: first, current online gambling regulation in Indonesia and Malaysia; second, Malaysia’s progressive legal experience as a blueprint for Indonesia; and third, social justice and SDGs-based online gambling regulation for Muslim-majority countries. A qualitative approach, including case studies, in-depth interviews with legal experts, and document analysis in both countries, was employed. The findings show that Malaysia’s implementation of progressive Islamic law has been effective in managing online gambling, promoting social justice, and reducing financial and mental health impacts. In contrast, weak law enforcement in Indonesia exacerbates the social issues related to online gambling. The research concludes that Malaysia’s approach has successfully regulated online gambling and supported SDG achievement. Therefore, Indonesia should consider adopting more progressive Islamic legal principles to enhance law enforcement and reduce the social harms of online gambling.